The Constitution and the Bill of Rights - Perrin, Pat; Coleman, Wim (Carlisle, Mass. : Discovery Enterprises, 2000)
Looks at the framing of the United States Constitution and its amendments through such primary source documents as speeches, records of the Constitutional Convention and similar meetings, and the documents themselves
Includes bibliographical references (p. 56)
Keywords: United States. -- Juvenile literature; United States. -- Sources; Constitutional history -- United States -- Juvenile literature; Constitutional history -- United States -- Study and teaching (Elementary); Constitutional history -- United States -- Sources; United States -- Politics and government -- 1783-1789 -- Juvenile literature; United States -- Politics and government -- 1783-1789 -- Study and teaching (Elementary); United States -- Politics and government -- 1783-1789 -- Sources